2011
DOI: 10.1186/1476-0711-10-18
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity island cag, vacA and IS605 genotypes in Mexican strains of Helicobacter pylori associated with peptic ulcers

Abstract: BackgroundHelicobacter pylori is associated with chronic gastritis, peptic ulcers, and gastric cancer. Two major virulence factors of H. pylori have been described: the pathogenicity island cag (cag PAI) and the vacuolating cytotoxin gene (vacA). Virtually all strains have a copy of vacA, but its genotype varies. The cag PAI is a region of 32 genes in which the insertion of IS605 elements in its middle region has been associated with partial or total deletions of it that have generated strains with varying vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 30 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Discordance in the frequency of cag PAI intactness in many reports was due to the different cag PAI genes being examined. 13 , 25 , 26 Thus, results of the present study indicate that deletions can occur in all parts of the cag PAI and screening the entire genes in the cag PAI is essential for an accurate determination of the organization of the cag PAI region. For comparison with our results, we reviewed only studies that screened all the cag PAI genes.…”
Section: Discussionmentioning
confidence: 76%
“…Discordance in the frequency of cag PAI intactness in many reports was due to the different cag PAI genes being examined. 13 , 25 , 26 Thus, results of the present study indicate that deletions can occur in all parts of the cag PAI and screening the entire genes in the cag PAI is essential for an accurate determination of the organization of the cag PAI region. For comparison with our results, we reviewed only studies that screened all the cag PAI genes.…”
Section: Discussionmentioning
confidence: 76%
“…However, a recent study has suggested that IS605 is not related to the cag -PAI status [26]. In a previous study involving the Taiwanese population, all isolates were reported as positive for the cag -PAI, but only 36% of these isolates carried an IS605 insertion [21].…”
Section: Discussionmentioning
confidence: 99%
“…In their study, few cagPAI genes (cagE, cagL, cagT and HP521) were examined to detect the intactness of cagPAI region. Discordant in the frequency of cagPAI intactness in many reports was due to the difference cagPAI genes that being examined [14,27,28]. Thus, results of the present study indicate that deletions can occur in all parts of the cagPAI and screening the entire genes in the cagPAI is needed to determine the accurate organization of the cagPAI region.…”
Section: Discussionmentioning
confidence: 56%